1976
DOI: 10.23986/afsci.71909
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of formaldehyde from feed to milk during the feeding of fresh cut grass treated with formaldehyde-containing preservative

Abstract: Abstract. 6 cows were fed for 2 weeks with fresh cut grass treated with formaldehyde-containing preservative. The formaldehyde content of the treated grass, as fed, averaged 490 mg/kg fresh weight and the consumption was 32 -44 kg fresh material/ cow/day. The formaldehyde content of the milk rose rapidly from a pre-feed level of 0 to 0.6 -2.2 mg/kg, and fell to 0 immediately after the feeding period. The faeces and urine contained 150 260 and 16 -26 mg formaldehyde/kg fresh weight respectively during the feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The results showed that the formaldehyde content of the milk increased with the increase in the formaldehyde treatment level of the feeds. Similar results were obtained by BECK and GROSS (1973), KREULA and RAURAMAA (1976), and WRENN et al (1976).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results showed that the formaldehyde content of the milk increased with the increase in the formaldehyde treatment level of the feeds. Similar results were obtained by BECK and GROSS (1973), KREULA and RAURAMAA (1976), and WRENN et al (1976).…”
Section: Resultssupporting
confidence: 88%
“…Formaldehyde has been used for this purpose in silage preservation and in the treatment of protein concentrates. When such additives are used, it is important to know how they behave in the metabolism of the animal, and the excretion of formaldehyde in the milk, faeces and urine has been investigated in many experiments (BECK and GROSS 1973, KREULA and RAURAMAA 1976, WRENN et al 1976, KAEMMERER and KERBER 1977, KAUFMANN and LUPPING 1978, SYRJÄLÄ et ai. 1978).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in good agreement with those previously published in goats (Barry and Tome 1982) and in cows ) which indicate that a fraction of dietary formaldehyde used to protect dietary protein from ruminai degradation was recovered as free formaldehyde in milk. Such a transfer of formaldehyde from the diet to the milk has also been observed with formaldehyde used as silage preservative (Beck and Gross 1974, Kreula and Rauramaa 1976, Arnould et al 1978, whey preserver Fisher 1984, Buckley etal. 1988) or as a protective agent of fats from rumen degradation (Wrenn et al 1975).…”
Section: Discussionmentioning
confidence: 82%
“…Some absorbed formaldehyde is transformed into various metabolites found in tissues (Mills et al 1972), milk (Mills et al 1972, Kreula and and urine (Neely 1964, Mills et al 1972. At least small amounts of formaldehyde are found in milk of ruminant fed formaldehydecontaining silages (Beck and Gross 1973, Kreula and Rauramaa 1976, Arnould et al 1978, or formaldehyde-protected proteins Tome 1982, Syrjälä-Qvist and.…”
Section: Introductionmentioning
confidence: 95%
“…The volatile fatty acids (VFA) and their effect on the silage dry matter content were taken into account according to ULVESLI and BREIREM (1960). The formaldehyde content of the urea, silage and milk was determined by the method of BECK and GROSS (1973) with the modification of AOAC (ANON 1975, see also KREULA andRAURAMAA 1976).…”
Section: Methodsmentioning
confidence: 99%